Γ‐Brasses with Spontaneous Magnetization: Atom Site Preferences and Magnetism in the Fe‐Zn and Fe‐Pd‐Zn Phase Spaces12. Issue 2 (15th December 2014) - Xie, Weiwei; Liu, Jing; Pecharsky, Vitalij; Miller, Gordon J.
Abstract The γ‐brasses in the binary Fe‐Zn system were re‐examined as part of the discovery of a new series of Fe‐Pd‐Zn γ‐brass compounds in the Zn‐rich region of the Fe‐Pd‐Zn phase space. Fe2+xZn11–x, x = 1.60(4)–1.99(9), and FexPd2.2–yZn10.8–x+y, x = 0.08(5)–2.46(8); y = 0.00(1)–1.44(4), all crystallize in the cubic crystal system, space group I<alternatives> <![CDATA[$\bar{4}$]]> <inline-graphic xlink:href="ark:/27927/pgh3xswfk87" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>3m, with corresponding ranges of the lattice parameter of 8.977(1)–8.979(1) Å and 9.1028(4)–9.0347(2) Å as x increases, as determined by single‐crystal X‐ray diffraction. In the binary Fe‐Zn system, iron atoms preferentially occupy the outer tetrahedron (OT) sites and partially mix with zinc atoms at the inner tetrahedron (IT) sites in the 26‐atom γ‐brass clusters. At the refined upper limit of Fe content, Fe atoms also replace Zn atoms at the octahedron (OH) sites. For the ternaries FexPd2.2–yZn10.8–x+y, refined site occupancies revealed three distinct patterns: (i) at low Fe content (x < 0.2), Fe/Pd and Pd/Zn mixing occurs, respectively, at the OT and OH sites; (ii) at intermediate Fe content (x ≈ 0.7), Fe/Pd and Fe/Zn mixing occurs, respectively, at the OT and IT sites; and (iii) at high Fe content (x > 0.9), Fe mixes at the IT (with Zn), OT (with Pd), and OH (with Zn) sites. Magnetization measurements of the Fe‐rich (x > 0.9) ternary phases indicate ferromagnetic or ferrimagnetic responses, which are consistent with the results of electronic structure calculations on "FePdZn11" used to model this phase. In addition, a Mulliken population analysis of the different sites in the 26‐atom γ‐brass cluster also provide a rationale for the complex behavior of atomic site occupancies vs. composition in both Fe2+xZn11–x and FexPd2.2–yZn10.8–x+y.